In Favor of Teachers Dignity - Knežić, Branislava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2006)
The following text is an attempt to pay attention to those who unjustifiably became subjects of various forms of verbal, and not rarely physical violence too. Those people are teachers. Illegal violation of their professional as well as human dignity is present for some time. We are afraid that when we are, not without reasons, worried for lives and rights of pupils, we are forgetting those (teachers, educators, pedagogues, professors) who made them and us, literate.